REAL-LIFE READING: A SYSTEMATIC REVIEW - Wahdaniyah, Risma; Fadillah, Akbar Nabil; Andriana, Reva Putri; Tarihoran, Naf'an (SIMPLE: International Journal of English Education, 2025)
Real-life reading, which is defined as reading that takes place in regular situations outside of controlled environments, is examined in this systematic study. The study's objectives are to determine the variables affecting these behaviors, analyze the approaches taken, and point out areas that require more investigation. A thorough database search was carried out using PRISMA criteria and keywords like "real-life reading" and "everyday reading." Laboratory-based research were removed, while those that focused on naturalistic reading behaviors were included. Key findings, methods, participant demographics, and objectives were all covered in the data extraction process. Three primary themes emerged from the review: (1) Contextual Factors: Situational and environmental factors have a big impact on reading habits; (2) Technological Influences: Digital devices have changed how people read; and (3) Methodological Challenges: Studying real-life reading is made more difficult by problems like ecological validity and participant variability. The results indicate that reading in real life is dynamic and context-dependent, although there are no established approaches in the literature. To properly record natural reading activities, new technologies are required, such as digital logs and wearable eye-trackers. To improve generalizability, future research should also examine a variety of populations and environments. By highlighting the significance of closing gaps between research and practical reading behaviors, these insights can guide interventions, technological design, and instruction to increase everyday reading engagement.